2014
DOI: 10.1007/s10327-014-0557-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gambian and Malian sorghum germplasm against downy mildew pathogen, Peronosclerospora sorghi, in Mexico and the USA

Abstract: The recent outbreak of sorghum downy mildew (SDM) in Texas, USA caused by pathotype P3 of Peronosclerospora sorghi, which is resistant to standard fungicide seed treatment, and the subsequent development of a new pathotype, P6, that overcame resistance in some hybrids, has emphasized the importance of continuing to develop new sources with genetic resistance. Eighty-two exotic Gambian and Malian germplasms and 10 sorghum lines commonly used as SDM pathotype differentials were field-evaluated in a randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…These variations could be attributed to genetic differences among the genotypes and the interaction effects are primarily due to the observed significant differences in disease pressure at both locations. Kamala et al (2002) and Prom et al (2010Prom et al ( , 2014 reported similar variation among sorghum genotypes response to SDM disease.…”
Section: Variability Of Genotypes To Downy Mildew Diseasementioning
confidence: 73%
See 1 more Smart Citation
“…These variations could be attributed to genetic differences among the genotypes and the interaction effects are primarily due to the observed significant differences in disease pressure at both locations. Kamala et al (2002) and Prom et al (2010Prom et al ( , 2014 reported similar variation among sorghum genotypes response to SDM disease.…”
Section: Variability Of Genotypes To Downy Mildew Diseasementioning
confidence: 73%
“…These observations, coupled with emergence of P. sorghi pathotypes make the need for genetic resistance through breeding to be more efficient, sustainable, environmentally friendly and cost-effective management approach for SDM control (Radwan et al 2011). Numerous resistant lines of sorghum to SDM disease have been identified in countries other than Uganda (Miller et al 1992;Prom et al 2007), and reports of screening sorghum and maize germplasm against SDM disease are available in India (Kamala et al 2006), China (Prom et al 2007), Mexico and USA (Prom et al 2014) and Brazil (Barbosa et al 2004).…”
Section: Sorghummentioning
confidence: 99%
“…The colonization and cross‐contamination of inoculated endophytes in newly emerged plants were confirmed at different growth stages (20, 30, and 60 DAS) using the isolation method described previously. The seedling emergence at 10 DAS and 1,000‐seed weight were determined from each panicle at maturity (Prom et al , ). The plants were observed daily for disease infections as described previously, the disease incidence was recorded at 60 DAS, and the disease protection calculated using Equation .…”
Section: Methodsmentioning
confidence: 99%
“…Diseases such as downy mildew, grain molds, anthracnose, leaf blight, and rust are the important and widespread diseases in tropical and subtropical regions of the world that can cause severe epidemics, resulting in considerable yield losses in sorghum. Germplasm sources for resistance to these diseases have been reported, for example, for downy mildew (Karunakar et al 1994a;Prom et al 2007Prom et al , 2015Sharma et al 2010), grain molds (Bandyopadhyay et al 1988;Sharma et al 2010;Prom and Erpelding 2009;Cuevas et al 2016;Thakur et al 2008), anthracnose (Prom et al 2007(Prom et al , 2012Cuevas et al 2016;Sharma et al 2012;Erpelding 2012), leaf blight (Sharma et al 2012;Singh and Singh 2014), and rust (Sharma et al 2012;Cuevas et al 2012). Wild and weedy relatives of sorghums as sources for downy mildew resistance have been reported (Karunakar et al 1994b;Kamala et al 2002).…”
Section: Diseasesmentioning
confidence: 99%